2011
DOI: 10.5539/ijbm.v6n4p150
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion of Employment Flexibility in Nigeria’s Banking Industry: Its Nature, Extent and Causes

Abstract: The increasing globalization of the world economy in recent years has triggered debates on whether and to what extent organizations in non-Western countries will embrace Western-style HRM practices. In particular, the issue of employment flexibility has received considerable attention. This paper explores the level of diffusion of employment flexibility in the Nigerian banking industry, analyzing whether the organization of employment in the three locally-owned case study organizations is becoming more or less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In fact, McDonaldization leads to the reduction of labor to a commodity that can be purchased at will (Wu, 2009) so as to pay low wages and control employees, and this is evident in the sector where casual employees are contracted and disengaged without due compensation. Adeleye (2011) revealed that the effect of globalization has left many bankers sacked, and their positions replaced with casual and contract staff who are employed through outsourcing. He added that this is to frustrate Trade Union activities (control) of collective bargaining and with the intention of cost reduction (calculability) because they are paid lower than the permanent staff.…”
Section: The Irrationalities Of Casualization Of Labor Job Flexibilimentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, McDonaldization leads to the reduction of labor to a commodity that can be purchased at will (Wu, 2009) so as to pay low wages and control employees, and this is evident in the sector where casual employees are contracted and disengaged without due compensation. Adeleye (2011) revealed that the effect of globalization has left many bankers sacked, and their positions replaced with casual and contract staff who are employed through outsourcing. He added that this is to frustrate Trade Union activities (control) of collective bargaining and with the intention of cost reduction (calculability) because they are paid lower than the permanent staff.…”
Section: The Irrationalities Of Casualization Of Labor Job Flexibilimentioning
confidence: 99%
“…A feature of this employment is that the terms do not allow for unionism (control) and other benefits. Another feature is that they are often poorly paid (calculability; Adeleye, 2011; Adenugba & Oteyowo, 2012; Gunu & Olabisi, 2011).…”
Section: Mcdonaldization Of the Nigerian Banks And Job Insecuritymentioning
confidence: 99%
See 2 more Smart Citations